Gower's Vulgar tongue : Ovid, lay religion, and English poetry in the Confessio Amantis - McCabe, T. Matthew N. (JSTOR EBA., 2011)
After establishing his reputation as a literary author by means of his French and Latin verse, Gower came to recognise the possibilities which English held for serious poetry in the 1380s. This book gives sustained attention to the implications of this language choice for the form, readership, religious position, and lay authority of his best-known work, the Confessio Amantis. The author argues that in all of his moral-political-theological writings, Gower's stance as a satirist and publicist is more markedly lay, and more rhetorically momentous for reasons associated with this lay status, than is generally thought. But during the 1380s, the conditions for writing lay public poetry in English made the Confessio a truly remarkable feat, for Gower and for English poetry.